2016
DOI: 10.3847/0004-637x/823/1/35
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Intrinsic Optical/Near-Infrared Linear Polarization for V404 Cygni During Its Bright Outburst in 2015: Broadband Modeling and Constraint on Jet Parameters

Abstract: We present simultaneous optical and near-infrared (NIR) polarimetric results for the black hole binary V404 Cyg spanning the duration of its seven-day-long optically brightest phase of its 2015 June outburst. The simultaneous R-and K s -band light curves showed almost the same temporal variation except for the isolated (∼30-minute duration) orphan K s -band flare observed at MJD 57193.54. We did not find any significant temporal variation of polarization degree (PD) and position angle (PA) in both R and K s ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
1
23
2
Order By: Relevance
“…Infrared polarization has now been detected from several quiescent, outbursting, and persistently accreting black hole binaries, lending credence to this expectation (Russell & Fender 2008;Russell & Shahbaz 2014;Russell et al 2016;Chaty, Dubus, & Raichoor 2011). Unfortunately, here too the observational evidence is equivocal with some studies finding variable polarization, and others not, and characteristics that may be more consistent with scattering in a disc outflow rather than from jet synchrotron emission (Tanaka et al 2016;Lipunov et al 2016;Shahbaz et al 2016;Itoh et al 2017;Kosenkov et al 2017).…”
Section: Are Slow Variations Driven By Plasmon Ejections or Disc Irramentioning
confidence: 92%
“…Infrared polarization has now been detected from several quiescent, outbursting, and persistently accreting black hole binaries, lending credence to this expectation (Russell & Fender 2008;Russell & Shahbaz 2014;Russell et al 2016;Chaty, Dubus, & Raichoor 2011). Unfortunately, here too the observational evidence is equivocal with some studies finding variable polarization, and others not, and characteristics that may be more consistent with scattering in a disc outflow rather than from jet synchrotron emission (Tanaka et al 2016;Lipunov et al 2016;Shahbaz et al 2016;Itoh et al 2017;Kosenkov et al 2017).…”
Section: Are Slow Variations Driven By Plasmon Ejections or Disc Irramentioning
confidence: 92%
“…These changes in the optical spectra led Muñoz-Darias et al (2016) to suggest that a short-lived nebular phase was triggered around this time. Tanaka et al (2016) observed V404 Cyg at various epochs between MJD 57190-57194 and did not find any evidence of intrinsic optical or NIR linear polarization, or any significant change in the amount of polarization or the polarization position angle. However, observations made between MJD 57191.62-57191.84 using the MASTER robotic telescope network showed a 4%-6% change in the optical linear polarization (Lipunov et al 2016).…”
mentioning
confidence: 87%
“…A lack of optical and near-infrared polarisation was reported by Tanaka et al (2016) in two periods during the outburst. There was, however, evidence of a strong contribution of synchrotron emission related to jet ejections in some other epochs (Rodriguez et al 2015;Martí et al 2016;Shahbaz et al 2016;Lipunov et al 2016;Bernardini et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…During the 1989 outburst, short-term X-ray variability was observed (e.g., Życki et al 1999). On June 15th in 2015, it underwent a short outburst after 26 years of quiescence (Barthelmy et al 2015a) and showed large flares in radio (Mooley et al 2015;Tetarenko et al 2015), infrared (Tanaka et al 2016), optical (Rodriguez et al 2015;Martí et al 2016;Gandhi et al 2016), X-ray (King et al 2015;Natalucci et al 2015;Negoro et al 2015;Segreto et al 2015;Walton et al 2017;Radhika et al 2016;Jourdain et al 2017;Huppenkothen et al 2017) and gamma-ray wavelengths (Roques & Jourdain 2016;Siegert et al 2016;Jenke et al 2016;Loh et al 2016;Piano et al 2017).…”
Section: Introductionmentioning
confidence: 99%